Environmental Risk Assessment of Genetically Modified Organisms: Volume 3. Methodologies for Transgenic Fish - Kapuscinski, Anne R (CABI, 2014)
This book is the outcome of a scientific partnership between the STAP and the WorldFish Center of the Consultative Group on International Agriculture Research (CGIAR). The book also benefited from scientific and strategic advice from relevant experts at the Secretariat of the Convention on Biological Diversity, the Food and Agriculture Organization of the United Nations and other organizations listed in the acknowledgements. Preparation of the book began with a book-drafting workshop led by the STAP, which conducted an independent, international and anonymous scientific peer review. To assure independence of the peer review, a guest series editor (E.M. Hallerman) replaced one of the series editors (A.R. Kapuscinski), who served as a subject matter editor for this volume.